KARAKTERISTIK PENDERITA HIPERTENSI YANG DIRAWAT INAP DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN KABUPATEN TAPANULI SELATAN 2010-2011 - Satria Muharram Dalimunthe; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Hypertension is one of the degenerative disease a public health problem in the world because hypertension often appears without symptoms. In Indonesia, patient of hypertension pursuant to Researching Into Health of Base ( Riskesdas) 2007 hypertension prevalensi in Indonesia very high, namely reach 31,7% from totalizeing the amount of adult resident. higher Hypertension Prevalence in Indonesia in comparison with tired Singapore 27,3%, Thailand by 22,7% and tired Malaysia 20%. But so many one who do not know and realize that x'self suffer hypertension. To know characteristic of patient of taken care of hypertension lodge in RSUD Town of Padangsidimpuan, have been conducted by research have the character of descriptive with series case desain continued with analysis of statistic. Population and of sampel amount to 165 patient of hypertension take care of to lodge. From the record data, the result obtained of proportion patient of highest woman in the age group 57-64 year ( 15.2%), Islam ( 77.6%), SLTA ( 40%), officer of private sector ( 39.4%), married ( 69.7%), Town of Padangsidimpuan ( 92.7%), headache ( dizzy, confused ) and weaken ( 35.8%), degree of hypertension 3 ( 45.4%), without comorbidity ( 72.1%), stroke ( 60.9%), average length of stay 4.07 days, medically discharged and becoming out patient ( 72.7%), there is no significant difference between age with the degree of hypertension ( p=0,078), there is significant difference between especial sigh with the degree of hypertension ( p=0,000), there is significant difference between average length of stay with the degree of hypertension ( p=0,000), there is significant difference between degree of hypertension with the desease comorbidity (p=0,000), there is significant difference between degree of hypertension with the situation of time went home ( p=0,003) Keywords : hypertension, patient characteristic, General Hospital Area Town of Padangsidimpuan